PolarTrack: Optical Outside-In Device Tracking that Exploits Display Polarization - Rädle, Roman; Jetter, Hans-Christian; Fischer, Jonathan; Gabriel, Inti; Klokmose, Clemens N.; Reiterer, Harald; Holz, Christian (Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
PolarTrack is a novel camera-based approach to detecting and tracking mobile devices inside the capture volume. In PolarTrack, a polarization ﬁlter continuously rotates in front of an off-the-shelf color camera, which causes the displays of observed devices to periodically blink in the camera feed. The periodic blinking results from the physical characteristics of current displays, which shine polarized light either through an LC overlay to produce images or through a polarizer to reduce light reﬂections on OLED displays. PolarTrack runs a simple detection algorithm on the camera feed to segment displays and track their locations and orientations, which makes PolarTrack particularly suitable as a tracking system for cross-device interaction with mobile devices. Our evaluation of PolarTrack’s tracking quality and comparison with state-of-the-art camera-based multi-device tracking showed a better tracking accuracy and precision with similar tracking reliability. PolarTrack works as standalone multi-device tracking but is also compatible with existing camera-based tracking systems and can complement them to compensate for their limitations.